Kedudukan Pajak dalam Transaksi Ekspor: Memahami Kewajiban PPN bagi Pengusaha di Indonesia - Fredlyna, Aurellia Mirabel; Permatasari, Nian Puspita; Oktasani, Reda; Azzahra, Aisyah (Cattleya Darmaya Fortuna, 2025)
This study discusses the position of tax in export transactions with a focus on understanding the Value Added Tax (VAT) obligations for entrepreneurs in Indonesia. This study was conducted to answer various questions related to the implementation and compliance of taxes in export transactions, considering the importance of the export sector in national economic growth. This topic was chosen based on the high relevance between tax regulations and the role of exports in driving the economy. Using the normative legal method approach and literature study, this study aims to understand the implementation of VAT rules for export entrepreneurs. The main findings show that although the VAT policy on exports is classified as goods or services that are not subject to tax, there are still gaps in its implementation due to the low understanding of entrepreneurs regarding tax rules and obligations. This study contributes by providing guidance to improve tax compliance and providing additional insights for regulators to clarify the rules to reduce potential non-compliance. In conclusion, this study highlights the importance of tax education and policy reform to create a more efficient and transparent export tax system.